Analisis Efektivitas Penggunaan Software Atlas Terhdap Pendukung Kinerja Auditor Di Kap Abc - Akbar Susilo Adi (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This research was conducted to determine the effectiveness of using ATLAS software to support auditor performance as measured by quality and quantity. In this research, the methodology used is descriptive qualitative research based on theoretical studies, results of previous research, interviews and observations of KAP ABC auditors. From this research, ATLAS software has an influence on supporting auditor performance by detecting misstatements and applicable general standards, then ATLAS plays a role in the audit process with the help of technology that is automatically and integrated, resulting in effective audits. So it can be concluded that software ATLAS effective in supporting auditor performance.